CHẤT LƯỢNG GIẤC NGỦ VÀ MỘT SỐ YẾU TỐ LIÊN QUAN TRÊN BỆNH NHÂN THOÁI HÓA CỘT SỐNG THẮT LƯNG TẠI BỆNH VIỆN Y HỌC CỔ TRUYỀN CẦN THƠ (Vietnam Journal of Community Medicine, 2026)
Objective: To assess sleep quality and related factors in patients with lumbar spondylosis. Materials and Methods: A cross-sectional descriptive study was conducted on 90 patients diagnosed with lumbar spondylosis. Sleep quality was evaluated using the Pittsburgh Sleep Quality Index (PSQI). Results: The mean age of the patients was 59.73 ± 12.46 years. Females accounted for the majority of the study population (71.1%). Most patients resided in rural areas (82.2%), and the predominant occupations were manual laborers (46.7%) and homemakers (24.4%). Regarding clinical characteristics, 76.7% of patients presented with nerve root compression. The duration of disease longer than 6 months accounted for 72.2% of cases. Most patients experienced moderate to severe pain based on the Visual Analog Scale (VAS). The mean PSQI score was 7.14 ± 1.53. Poor sleep quality was observed in 84.4% of the patients. Sleep quality was significantly associated with age, pain severity assessed by VAS, fatigue, stress, and anxiety (p < 0.05). Conclusion: Poor sleep quality is highly prevalent among patients with lumbar spondylosis. Sleep quality is significantly associated with older age, pain severity, fatigue, stress, and anxiety.
Keywords: Sleep quality, Lumbar spondylosis, Pittsburgh Sleep Quality Index (PSQI)